UKRAINE ENERGY MARKET : CREATION OF CONDITIONS FOR EFFECTIVE ENERGY SUPPLY - KOHUT, Sergey (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the theoretical foundations of the formation of energy security on the energy market of Ukraine in the context of European integration processes, and states that energy security is a component of the state’s national security. The main advantages of long-term contracts for all energy market participants are indicated. Features of the functioning of consumer companies in the competitive market are highlighted. The main risks for large consumers when working on the day-ahead market are presented. Factors of the expediency of functioning on the balancing segment are given. Current trends in the development of world energy and their impact on energy security are analyzed. The necessity of diversification of energy supply sources for Ukraine is substantiated. The influence of the European integration processes on the reform of the energy sector of Ukraine is studied. The current state of the energy market was analyzed, and the analysis of factors affecting development trends and ensuring protection in the energy market was carried out. The influence of the European integration processes on the reform of the energy sector of Ukraine is studied. The conjuncture of the energy market of Ukraine is determined, in which it is necessary to analyze not only the peculiarities of the domestic sphere, but also the influence of international relations, international trade and the world market. The PEST analysis of the energy industry of Ukraine is presented, which allowed to identify the level of influence and the neighborhood of the group of influencing factors on the formation of the strategic potential of the energy market of Ukraine. Directions for increasing the level of energy security through modernization of the energy infrastructure, development of renewable energy sources, and integration into the European energy space are proposed. It is noted that the creation of conditions for the effective use of internal resources and the development of appropriate technologies are of strategic importance. The country’s government is working on integration into the European energy community, which requires compliance with European standards and the implementation of effective management models of the energy market of Ukraine. According to the results of the strategic potential of the energy industry of Ukraine, economic factors exert the greatest influence - 1.147, which just emphasizes the important role of the energy industry in the country’s economy. In second place in terms of influence are political factors - 0.847. The analysis of the market just showed the rather important role of the political component in the functioning of the energy market of Ukraine, namely in the aspect of its joining the European energy market and the transformation of Ukraine into the European Union with the rights of an equal state. In third place are technological factors - 0.553, which confirm Ukraine’s determination to decarbonize the energy market. And the fourth place is occupied by socio-cultural factors - 0.537, which are only marginally inferior to technological factors. This indicates a strong influence of consumer preferences when choosing interaction models in the market.